Non-coding RNAs as key regulators of epithelial-mesenchymal transition in breast cancer - Peng, Jing; Liu, Wenhui; Tian, Jiaju; Shu, Yuncong; Zhao, Rui; Wang, Yuping (Frontiers in Cell and Developmental Biology, 2025)
This study examines the critical role of non-coding RNAs (ncRNAs) in regulating epithelial-mesenchymal transition (EMT) in breast cancer, a prevalent malignancy with significant metastatic potential. EMT, wherein cancer cells acquire mesenchymal traits, is fundamental to metastasis. ncRNAs—such as microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs)—modulate EMT by influencing gene expression and signaling pathways, affecting cancer cell migration and invasion. This review consolidates recent findings on ncRNA-mediated EMT regulation and explores their diagnostic and therapeutic potential. Specifically, miRNAs inhibit EMT-related transcription factors, while lncRNAs and circRNAs regulate gene expression through interactions with miRNAs, impacting EMT progression. Given the influence of ncRNAs on metastasis and therapeutic resistance, advancing ncRNA-based biomarkers and treatments holds promise for improving breast cancer outcomes.